Dinamika Pertumbuhan dan Potensi Keuangan Syariah dalam Mewujudkan Ekonomi Nasional yang Berkelanjutan - Zalfa Khoirun Nisa; Fadilatur Rohmah; Rosiana Aolia Safitri; Fisit Suharti (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2026)
The Islamic financial sector in Indonesia has demonstrated an increasingly strategic role in supporting inclusive and sustainable economic growth. Although the assets of Islamic banking have exceeded IDR 1,050 trillion as of March 2026, its market share remains relatively small, at approximately 7.5%–8%, indicating that its potential has not yet been fully optimized. This study aims to analyze the development of the Islamic financial sector, identify key challenges—particularly in terms of financial literacy and digital transformation—and formulate strategies to strengthen institutional capacity in the digital economy era. This research employs a descriptive qualitative approach through a literature review, utilizing secondary data from the Financial Services Authority (OJK), Bank Indonesia, and the National Committee for Islamic Economy and Finance for the 2024–2026 period. The findings reveal a gap between asset growth and the relatively low level of public literacy, as reflected in a literacy index of 39.11%, which is lower than the inclusion rate. This gap gives rise to the phenomenon of the floating mass, which may reduce customer loyalty. In addition, digital transformation plays a crucial role in expanding access to financial services and addressing competition from fintech. The study also highlights the importance of industry consolidation, the integration of social and commercial financial instruments, and the strengthening of the real sector, particularly MSMEs. Overall, the development of Islamic finance requires integrated policy support, enhancement of human capital quality, and optimization of digital technology to strengthen its competitiveness and contribution to the national economy.